Having a baby in your 40s with assisted reproductive technology: The reproductive dilemma of autologous versus donor oocytes. (18th May 2020) - Hogan, Rosemarie G.; Wang, Alex Y.; Li, Zhuoyang; Hammarberg, Karin; Johnson, Louise; Mol, Ben W.; Sullivan, Elizabeth A.
Abstract : Background: Increasing numbers of women ≥40 years old are accessing assisted reproductive technology (ART) due to age‐related infertility. There is limited population‐based evidence about the impact on the cumulative live birth rate (CLBR) of women aged ≥40 years using their own oocytes, compared to women of a similar age, using donor oocytes. Aims: To compare the CLBR for women ≥40 years undergoing ART using autologous oocytes and women of similar age using donor oocytes. Materials and Methods: This population‐based retrospective cohort study used data from all women aged ≥40 years undergoing ART with donated ( n = 987) or autologous oocytes ( n = 19 170) in Victoria, Australia between 2009 and 2016. A discrete‐time survival model was used to evaluate the CLBR following ART with donor or autologous oocytes. The odds ratio, adjusted for woman's age; male age; parity; cause of infertility; and the associated 95% confidence intervals (CI), were calculated. The numbers needed to be exposed (NNEs) were calculated from the adjusted odds ratio (aOR) and the CLBR in the autologous group. Results: The CLBR ranged from 28.6 to 42.5% in the donor group and from 12.5% to 1.4% in the autologous group. The discrete‐time survival analysis with 95% CI demonstrated significant aOR on CLBR across all ages (range aOR: 2.56, 95% CI: 1.62–4.01 to aOR: 15.40, 95% CI: 9.10–26.04). Conclusions: Women aged ≥40 years, using donor oocytes had a significantly higher CLBR than women using autologous oocytes. The findings can be used when counselling women ≥40 years about their ART treatment options and to inform public policy.